First Presentation of an Acquired Demyelinating Syndrome - Gottlieb-Smith, Rachel; Waldman, Amy T. (Journal of Pediatric Neurology, 2018)
Acquired demyelinating syndromes (ADS) present with acute or subacute monofocal or polyfocal neurologic deficits localizing to the central nervous system. The clinical features of distinct ADS have been carefully characterized including optic neuritis, transverse myelitis, and acute disseminated encephalomyelitis. These disorders may all be monophasic disorders. Alternatively, optic neuritis, partial transverse myelitis, and acute disseminated encephalomyelitis may be first presentations of a relapsing or polyphasic neuroinflammatory disorder, such as multiple sclerosis or neuromyelitis optica. The clinical features of these disorders and the differential diagnosis are discussed in this article.
Keywords: optic neuritis; transverse myelitis; acute disseminated encephalomyelitis